2012
DOI: 10.1007/s00425-012-1673-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three auxin-inducible LBD members on lateral root formation in Arabidopsis thaliana

Abstract: In Arabidopsis, two Auxin Response Factors (ARF7 and ARF19) and several Aux/IAAs regulate auxin-induced lateral root (LR) formation. As direct targets of ARF7 and ARF19, Lateral Organ Boundaries Domain 16 (LBD16), LBD29, and LBD18 have a biological function in the formation of lateral roots (LRs). However, the details of the functions of these three LBDs have remained unclear. Each single T-DNA insert mutant has been shown to have slightly fewer LRs than the wild type. We then created a triple mutant, which ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 40 publications
3
64
0
Order By: Relevance
“…It was previously reported that several LBD genes participate in lateral root formation (Berckmans et al, 2011;Feng et al, 2012aFeng et al, , 2012bLee et al, 2012). During the initiation of root primordia, LBD18 was found to regulate the cell cycle-controlling gene E2Fa and the cell wall-loosening factor gene EXPANSIN14 (Berckmans et al, 2011;Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that several LBD genes participate in lateral root formation (Berckmans et al, 2011;Feng et al, 2012aFeng et al, , 2012bLee et al, 2012). During the initiation of root primordia, LBD18 was found to regulate the cell cycle-controlling gene E2Fa and the cell wall-loosening factor gene EXPANSIN14 (Berckmans et al, 2011;Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Quadruple mutants in four cytokinin biosynthesis genes [ISOPENTENYL TRANSFERASE1 (IPT1), IPT3, Specified by high cytokinin response [23] Antagonistic transcriptional crosstalk Quiescent centre founder cell Low auxin response limits ARR7 and ARR15 transcription to give a high cytokinin response [23] Specified by high cytokinin response [23] Antagonistic transcriptional crosstalk Lateral root founder cell Auxin response minimum [17] and then an oscillating auxin response primes founder cells [26]. Auxin response maximum specifies lateral root founder cells [2,29,31,32] and activates lateral root founder cells via cell division [34] Low cytokinin response allows priming [37,38] and correct PIN1 localisation [41][42][43]. Inhibits founder cell activation [39] Cross-regulation of the cell cycle.…”
Section: Trends In Plant Sciencementioning
confidence: 99%
“…Founder cell specification is dependent on transcription of the GATA23 transcription factor by IN-DOLE-3-ACETIC ACID INDUCIBLE 28 (IAA28) and ARF7/19 [31], whereas nuclear polarisation and asymmetric cell division include bimodal auxin signalling pathways: comprising BODENLOS (BDL)/IAA12 and MONO-PTEROS (MP/ARF5), or SOLITARY ROOT/IAA 14 and ARF7/19 [32]. Auxin promotes cell cycle progression at the G1-S checkpoint via LATERAL ORGAN BOUNDARY gene induction by ARF7 and 19 [33,34], which in turn activates D-type cyclins. In addition, CYCLIN-DEPEN-DENT KINASE A and D-TYPE CYCLIN 2;1 (CYCD2;1) expression is released from repression by INHIBITOR OF CDK2/KIP-RELATED PROTEIN 2 [35,36].…”
Section: Lr Initiation: the Pairwise Specification Of Founder Cellsmentioning
confidence: 99%
“…Similarly, slr/iaa14 root explants could be induced to form shoots upon sequential treatment with CIM and shootinducing media, indicating that callus formation could also be promoted through manipulation of cell division and hormone levels (Atta et al, 2009). LBD16, LBD18 and LBD29, the functions of which have not been specifically defined but are known to occur downstream of auxin signaling, are also implicated in both LR initiation and callus formation (Fan et al, 2012;Feng et al, 2012). Additionally, ALF4, which is required for division of LRFCs and appears to function independently of auxin signaling (Celenza et al, 1995;DiDonato et al, 2004), is also required for callus formation as alf4 mutants cannot be induced to form callus tissue from either root or shoot explants (Sugimoto et al, 2010).…”
Section: Lr Formation: Parallels With Callus Formationmentioning
confidence: 99%